Design of solvent-free functional fluids via molecular nanoarchitectonics approaches. Issue 1 (18th January 2019) - Shinohara, Akira; Pan, Chengjun; Wang, Lei; Nakanishi, Takashi
Abstract : This minireview highlights the recent achievements in the development of solvent-free functional fluids based on molecular/polymeric design approaches. Abstract : Solvent-free functional fluidic materials have recently attracted considerable attention owing to their high deformability and facile processability. The counterintuitive softness of functional organic molecules/materials that are intrinsically rigid, such as polycyclic hydrocarbons, aromatic macrocycles, fullerenes, and conjugated polymers, is a significant advantage towards various softness-oriented applications. For example, the development of optoelectronically active fluids has shifted the attention from hard matter-based devices that barely bend and stretch under actions required in flexible/stretchable electronics. This minireview presents a summary of the latest reports and current challenges of functional molecular/polymeric fluids from their molecular engineering approaches or the nanoarchitectonics of functional fluids to the state-of-the-art functions derived from the fluids.